Uma escola inclusiva de referência no contexto da educação especial no estado de Goiás: um estudo de caso - ALMEIDA, Gisella de Souza (2006)
This study seeks to understand the process of implementation and results of the Inclusive Education Proposal into the mainstream education system of the Goiás State. The Superintendence of Special Education, which is a sector of the State Secretariat of Education, is responsible for this proposal. By using a case study, this study looks at the Inclusive School of Reference (Escola Inclusiva de Referência EIR) located in the capital of the state, that is, the Goiânia city. Since 1999, the State Government of Goiás, implemented the Educating for Diversity State Programme that aims to disseminate and implement the national guidelines for inclusion. The Inclusive School of Reference is a central organization in developing this policy. Considering this, this study reviews the development of special education policy in the state of Goiás from 1990 as well as it describes and analyses how the inclusive education proposal happens into the school and in its classrooms. Data has been gathered by using observation, formal and informal interviews, documental analysis and other information collected in the school. A qualitative descriptive and reflective analysis of the data has been carried out by adopting the theoretical and methodological framework of the Phenomenology, by which the study tries to understand the school as a phenomenon in the field. Throughout the study, then, numerous questions have emerged, amongst these, what is an inclusive school of reference? Can the State of Goiás School of Reference be considered a reference? Why? Is Education, in its own rights, inclusive? Finally, perceptions and perspectives are enlightened by the study as a means to contribute to push inclusive education forward.